The housing preference of young people in Malaysian urban areas: a case study Subang Jaya, Selangor - Ling, Oliver Hoon Leh; Nurul Amanina Mansor,; Siti Nur Afiqah Mohamed Musthafa, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
A house is a basic shelter. This simple definition of a house has become wider as it assumes a social status symbol and an economic property value while serving the various inter-linked functions of protection, neighbourhood, social interactions, community amenities and services, privacy, and access to work. However, young Malaysian urbanites are feeling restricted by current housing options as they confront the difficulties of owning a house in urban areas due to the current much inflated housing prices. This study investigated the housing preferences of urban young people in USJ 1, Subang Jaya. Primary data were gathered from a total of 99 male and female respondents aged 20 to 39 years who were sampled from nine condominiums, apartments and housing parks. The findings revealed that most young Malaysian urbanites preferred landed housing with more number of bedrooms to high-rise housing. They strongly preferred to purchase their future house that truly meets their housing preferences. In terms of location, these young people preferred to live in urban area so as to be close to their workplace and services. They targeted high priced houses despite their affordability issues.